2017
DOI: 10.1007/978-3-319-62773-1_3
|View full text |Cite
|
Sign up to set email alerts
|

Advanced Feeds for mm-Wave Antenna Systems

Abstract: Millimetre-wave antenna systems have traditionally required high performance feeds in order to fulfil its stringent requirements. Therefore, this goal has been achieved by corrugated horns. However, in the last years new applications mainly in the communication area have driven the use of other types of antenna feed with slightly reduced performance but simpler manufacturing and reduced cost. The simplicity of manufacturing is especially critical as frequency increases and in fact corrugated horns are extremel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 30 publications
(44 reference statements)
0
3
0
Order By: Relevance
“…Constant gain horns have previously been outlined by Olver [2], who pointed out that wide angle linear tapered horns had approximately constant gain for certain taper lengths over limited bandwidths, albeit with rather poor broad beam patterns. A highly compact design with a constant gain operating over 20% bandwidths has also been described for a body scanner application, with low sidelobes and cross-polar < -30 dB and return loss < -22 dB [4]. It can be shown that such a constant gain horn requires precise dispersive properties between modes and in Section IV we demonstrate a design that can operate over full waveguide bands with reasonable beam quality.…”
Section: E Constant Gain Hornsmentioning
confidence: 93%
See 1 more Smart Citation
“…Constant gain horns have previously been outlined by Olver [2], who pointed out that wide angle linear tapered horns had approximately constant gain for certain taper lengths over limited bandwidths, albeit with rather poor broad beam patterns. A highly compact design with a constant gain operating over 20% bandwidths has also been described for a body scanner application, with low sidelobes and cross-polar < -30 dB and return loss < -22 dB [4]. It can be shown that such a constant gain horn requires precise dispersive properties between modes and in Section IV we demonstrate a design that can operate over full waveguide bands with reasonable beam quality.…”
Section: E Constant Gain Hornsmentioning
confidence: 93%
“…Today, beam patterns from corrugated feedhorns can be modelled with extraordinary accuracy using mode matching software and there is now a significant literature on their design and optimization including a number of books and review articles [1], [2], [3], [4]. Often, initial designs are based on general geometric arguments and improved by computational optimization programs [5].…”
Section: Introductionmentioning
confidence: 99%
“…Commonly, mm-wave corrugated horns are fabricated by direct machining [9] or electroforming [10], but these fabrication techniques require medium to high cost and long delivery time. Recently developments propose the use of platelet technique to fabricate wideband mm-wave corrugated horns which is able to reduce the cost [11], [12], but the mechanical robustness during thermal cycling is one of the main concerns of this technique.…”
mentioning
confidence: 99%